Zoomorphic Metaphors and Similes in the Modern Russian Prose - Petrova, Zoya (Slavica, 2020)
The article represents the main circle of zoonymous images common in the modern Russian prose, they are classified into thematic groups of the “Animals” class, the most frequent vehicles of metaphors and similes are identified, the circle of tenors is outlined, distributed according to the relative frequency of use in literary texts. By means of comparison with the traditional images of the class in question, presented in the dictionary of metaphors and similes of the previous period of the Russian literature, and with the figurative uses of zoonyms in the Russian linguistic world image based on materials of linguocultural dictionaries, the main directions of evolution of zoomorphic tropes in modern Russian prose are determined. Some aspects of textual functioning of zoomorphic tropes are studied: individual preferences in choosing their groups, their conceptualizing role in the text. The results of the study make it possible to get an idea of ​​one fairly significant fragment of the figurative world image of the modern Russian prose.